A lithium slurry battery electrode and its component ratio screening method and application

By determining the influence law of the electrode components of lithium paste cells on conductivity, viscosity and gram capacity, the composition ratios of 8% lithium iron phosphate, 1% Kochen black, 2% TX-100 and 89% electrolyte were screened to solve the problem. The problem of lack of scientificity in the electrode composition ratio of lithium paste cells has improved the stability and selection efficiency of electrode performance, and provided a scientific basis for the industrial production of lithium paste cells.

CN119050273BActive Publication Date: 2025-02-14UNIV OF SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411415800.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-14
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The lack of scientificity and systematicity in the electrode distribution ratio of lithium paste cells in the prior art, resulting in unstable electrode performance and difficulty in achieving large-scale industrial production.

Method used

By determining conductivity, viscosity and gram capacity as key indicators for screening, we study the influence patterns of different components on these indicators, and then screen out the appropriate component distribution ratio. The specific composition ratio is: 8% lithium iron phosphate slurry, 1% Kochen black, 2% TX-100 and 89% electrolyte.

Benefits of technology

The scientific design and optimization of the electrode composition ratio of lithium paste cells has been realized, the stability and selection efficiency of electrode performance have been improved, and the scientific basis for the industrial production of lithium paste cells has been provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119050273B_ABST
    Figure CN119050273B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium slurry battery electrode and a screening method and application of its component ratio, belonging to the field of batteries. The lithium slurry battery electrode includes the following components in mass percentage: 8% lithium iron phosphate slurry, 1% Ketjen black, 2% TX‑100 and 89% electrolyte. The screening method includes: first, determining the specific indicators for component ratio screening - conductivity, viscosity and gram capacity according to the electrochemical performance requirements and working mode of the lithium slurry battery; then obtaining the effect of different components such as active materials, conductive agents, dispersants, electrolytes on conductivity, viscosity and gram capacity; finally, completing the screening of the optimal ratio of electrode components based on a comprehensive evaluation of the three types of indicators. The present invention provides a systematic and scientific component ratio design and optimization mechanism, improves the selection efficiency of the electrode component ratio, and provides a scientific basis for determining the content of lithium slurry battery electrode components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries and relates to a lithium slurry battery electrode and a screening method and application of its component ratio. Background Art

[0002] As a new type of battery, lithium slurry battery combines the characteristics of flow battery and lithium ion battery. Its electrode morphology is no longer solid, but semi-solid, which is consistent with flow battery; on the other hand, it can use the same positive and negative active materials as lithium ion battery, has the same electrochemical reaction mechanism as lithium ion battery, and its energy density is much higher than that of flow battery. Therefore, it has received widespread attention from scholars in recent years.

[0003] The industrial production technology of lithium-ion batteries is already very mature, and generally includes the following steps: precursor preparation, electrode preparation, assembly, packaging, etc. When preparing the pole piece of a lithium-ion battery, steps such as slurry preparation, slurry mixing, coating, drying, rolling, and cutting are required. However, the positive or negative electrode of a lithium slurry battery is a flowable semi-solid slurry (both the positive and negative electrodes can also be flowable semi-solid slurries), so the process of pole piece preparation is different from that of a lithium-ion battery. In addition, in the industrial production of lithium-ion batteries, in addition to the process of production process standardization, the content of each component in the electrode pole piece is also relatively fixed. The main components are generally: electrode material, conductive agent, binder, etc. When preparing batteries in the laboratory, the ratio of electrode material, conductive agent, and binder is generally 8:1:1; in industrial production, the ratio of electrode material, conductive agent, and binder is generally 9:0.5:0.5. For lithium slurry batteries, since they are still in the research and development stage and have not yet been put into large-scale industrial production, there is no clear reference standard from the main component composition to the ratio of each component. Summary of the invention

[0004] The present invention provides a method and application for screening lithium slurry battery electrodes and their component ratios. First, the specific indicators for component ratio screening, namely conductivity, viscosity and gram capacity, are determined; secondly, the effects of different components on conductivity, viscosity and gram capacity are obtained; finally, the component screening of the electrode component ratio is completed.

[0005] The present invention adopts the following technical solutions:

[0006] A lithium slurry battery electrode comprises the following components in percentage by mass: 8% lithium slurry, 1% conductive agent, 2% dispersant and 89% electrolyte.

[0007] In the above technical solution, the lithium slurry is lithium iron phosphate slurry, the conductive agent is Ketjen black, the dispersant is TX-100, and the electrolyte is a lithium bis(trifluoromethanesulfonyl)imide solution with a molar concentration of 1 mol / L, wherein the solvent is a mixture of dimethyl carbonate and ethylene carbonate, and the mixing ratio of dimethyl carbonate and ethylene carbonate is 7:3 (mass ratio). (The electrolyte includes but is not limited to this formula, and commercial electrolytes and other types of electrolytes are applicable).

[0008] A method for screening the composition ratio of lithium slurry battery electrodes comprises the following steps:

[0009] Step 1: Determine the key indicators for screening the composition ratio of lithium slurry battery electrodes - conductivity, viscosity and gram capacity;

[0010] Step 2: Obtain the effect of different electrode components on conductivity, viscosity and gram capacity;

[0011] Step three, according to the action rules obtained in step two, the electrode composition ratio of the lithium slurry battery is screened.

[0012] In the above technical scheme, in step one, the lithium slurry battery electrode is a slurry electrode composed of an electrode active material, a conductive agent and an electrolyte; the battery includes (1) both the positive and negative electrodes of the battery are slurry electrodes; (2) one of the positive and negative electrodes of the battery is a slurry electrode and the other is a traditional solid electrode; (3) positive electrode materials such as lithium iron phosphate, ternary nickel cobalt manganese, organic positive electrode active materials, etc.; negative electrode materials such as lithium titanate, graphite and silicon, etc.

[0013] In the above technical solution, in step 2, the different components of the electrode are lithium slurry, conductive agent, dispersant and electrolyte.

[0014] Beneficial effects:

[0015] The present invention discloses a lithium slurry battery electrode and a method for screening its component ratio. The lithium slurry battery electrode includes the following components in mass percentage: 8% lithium iron phosphate slurry, 1% Ketjen black, 2% TX-100 and 89% electrolyte. The lithium slurry battery electrode has better viscosity, conductivity and gram capacity than other lithium iron phosphate slurries with different component ratios in the experiment. The method for screening the component ratio of the lithium slurry battery electrode includes step one, determining the key indicators for screening the component ratio of the lithium slurry battery electrode - conductivity, viscosity and gram capacity; step two, obtaining the effect of different components of the electrode on conductivity, viscosity and gram capacity; step three, screening the electrode component ratio of the lithium slurry battery according to the effect law obtained in step two. The method provides a systematic and scientific component ratio design and optimization mechanism, improves the selection efficiency of the electrode component ratio, and provides a scientific basis for determining the content of the components of the lithium slurry battery electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Flow chart for screening the composition ratio of lithium slurry battery electrodes.

[0017] Figure 2a , Figure 2b , Figure 2c This shows the influence of different components and different contents of lithium iron phosphate / KB on the conductivity of lithium iron phosphate slurry.

[0018] Figure 3a , Figure 3b , Figure 3c , Figure 3d The effect of different TX-100 contents on the conductivity of lithium iron phosphate slurry.

[0019] Figure 4a , Figure 4b The relationship between viscosity and stress of TX-100 as shear rate changes.

[0020] Figure 5a , Figure 5b , Figure 5c The effect of different KB contents on the viscosity of lithium iron phosphate slurry.

[0021] Figure 6a , Figure 6b , Figure 6c The effect of different KB contents on the stress of lithium iron phosphate slurry.

[0022] Figure 7a , Figure 7b , Figure 7c , Figure 7d The effect of different TX-100 contents on the viscosity of lithium iron phosphate slurry.

[0023] Figure 8a , Figure 8b , Figure 8c , Figure 8d The figure shows the effect of different TX-100 contents on the stress of lithium iron phosphate slurry.

[0024] Figure 9a , Figure 9b , Fig.9c The effect of different contents of lithium iron phosphate on the viscosity of lithium iron phosphate slurry.

[0025] Fig.10a , Fig.10b , Fig.10c This shows the effect of different lithium iron phosphate contents on the stress of lithium iron phosphate slurry. DETAILED DESCRIPTION

[0026] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0027] Example

[0028] like Figure 1 As shown, a method for screening the composition ratio of lithium slurry battery electrodes comprises the following steps:

[0029] Step 1: Determine the key indicators for screening the composition ratio of lithium slurry battery electrodes - conductivity, viscosity and gram capacity;

[0030] Step 2: Obtain the effect of different electrode components on conductivity, viscosity and gram capacity;

[0031] Step three: Screen the electrode composition ratio of the lithium slurry battery based on the research results.

[0032] Step one is to determine the key indicators for screening the composition ratio of lithium slurry battery electrodes. This key indicator is designed based on the characteristics of lithium slurry battery electrodes.

[0033] Step 2 is to obtain the effect of different electrode components on conductivity, viscosity and gram capacity. The specific process is described below:

[0034] (1) Effect of electrode composition on conductivity:

[0035] Conductivity is a parameter used to describe the ease with which electric charges flow in a substance, and is also known as electrical conductivity. Taking lithium iron phosphate batteries as an example, the lithium iron phosphate in the positive electrode material is an olivine structure, and its space point group is Pnma. From the perspective of the crystal structure of lithium iron phosphate, a major problem when using it as a positive electrode material is: low electronic conductivity. In the crystal structure of lithium iron phosphate, electrons can generally only be conducted along the Fe-O-Fe bond when conducting, but the conduction path of electrons will be blocked by the non-conductive PO4 tetrahedron. Therefore, the conductivity of lithium iron phosphate itself is very low (about 10 -9 S / cm -10 -10S / cm). Therefore, when lithium iron phosphate is used as a positive electrode material, in order to improve its conductivity, it is generally carbon-coated. In addition, when preparing the electrode, a certain amount of conductive agent is generally added to improve the conductivity of the electrode. For lithium iron phosphate slurry, the role of the conductive agent is equally important. There are both solid-phase electronic conductivity and liquid-phase ionic conductivity in lithium slurry. Solid-phase electronic conductivity mainly relies on the conductive network for electron conduction, which is affected by the conductivity of the lithium slurry itself. The conductivity of lithium slurry is closely related to the composition ratio and the conductive network. Liquid-phase ionic conductivity is mainly affected by the characteristics of the electrolyte itself in the lithium slurry. Due to the high content of electrolyte in the lithium slurry, the ion conductivity is good. Therefore, it is necessary to pay attention to the effects of different components in the lithium slurry on conductivity, so as to screen out a suitable composition ratio.

[0036] Taking lithium iron phosphate slurry as an example, the effect of different electrode components on conductivity is obtained. The conductivity of lithium iron phosphate slurry can be obtained using a conductivity meter. As the lithium iron phosphate content increases, the conductivity of lithium iron phosphate slurry shows a downward trend. Conductive agents can form a stable conductive network in the electrode. The addition of the conductive agent, Ketjen black (KB), can improve the conductivity of lithium iron phosphate slurry. From the perspective of conductivity, the addition of conductive agents is also necessary. When the addition amount of KB is 0.5%, the conductivity of the slurry has not changed significantly; when the addition amount reaches 1%, the conductivity increases significantly, which has slightly exceeded the conductivity of the electrolyte itself. As the KB content increases, the conductivity will also increase. Dispersant TX-100 can make the solid particles in the solution dispersed evenly. For lithium iron phosphate slurry, it is to make the lithium iron phosphate and KB dispersed evenly, which can make the overall conductive network of the slurry dispersed evenly. Dispersant TX-100 within the appropriate content range can promote a more uniform conductive network of lithium iron phosphate slurry, but if its content is too high, it will have a negative impact on the conductivity of lithium iron phosphate slurry due to its own low conductivity.

[0037] (2) Effect of electrode composition on viscosity:

[0038] Fluid, unlike the common solid state, is a special form of matter. Fluids can be divided into two categories: gas and liquid. The electrode slurry of lithium slurry battery is a typical liquid fluid. An ideal fluid has no friction inside. But in reality, when the fluid flows relative to an object (such as the flow of lithium slurry), friction will always occur, which will hinder the movement of the fluid. At this time, the force that hinders the movement of the fluid - friction, is the special property of the fluid - viscosity. If the viscosity is too high, the friction is large when flowing, and it cannot flow smoothly. For the electrode slurry of lithium slurry battery, on the one hand, the electrode slurry flows back and forth from the liquid storage tank to the working area, so it needs to be able to flow smoothly and the viscosity cannot be too high; on the other hand, the electrode slurry needs to remain stable. If the viscosity is too low, the electrode slurry is prone to sedimentation. This requires the viscosity of the electrode slurry to be kept in an appropriate range so that it can remain sufficiently stable while being flowable.

[0039] Taking lithium iron phosphate slurry as an example, the effect of different electrode components on viscosity was obtained. The viscosity of lithium iron phosphate slurry can be obtained using rheometers and other types of viscosity characterization instruments. The influence of lithium iron phosphate content on slurry viscosity and stress is very significant. When the content of lithium iron phosphate doubles, the viscosity of the slurry increases by 1-2 times, and the stress increases by 3-5 times. The increase in KB content increases the viscosity of the slurry and increases the stress. Although the addition of KB can make the slurry less likely to settle and maintain a stable state, the continuous increase in KB will make the viscosity of the slurry too high and the fluidity reduced. At the same time, as the KB content increases from 1% to 2%, the stress of the slurry more than doubles. The increase in stress means that the circulating pump needs to do more work when the slurry circulates between the liquid storage tank and the working area, and this part of work is also an energy loss that cannot be ignored. Therefore, a KB content of 1% can maintain the slurry state and at the same time reduce the energy loss caused by the slurry during circulation. TX-100 can evenly disperse lithium iron phosphate and KB that are difficult to dissolve in the electrolyte, effectively weaken the sedimentation and coagulation of particles, and make the state of the suspension tend to be stable. But on the other hand, the relationship between the viscosity of TX-100 and the shear rate shows an obvious shear thickening phenomenon. If an excessive amount of TX-100 is added, the viscosity of the slurry will inevitably be too large, so it is also very important to control the content of TX-100. From the experimental results, it can be seen that the viscosity and stress of the slurry with the addition of TX-100 have increased; and the viscosity decreases at a slower rate as the shear rate increases. However, when the content of TX-100 increases to 4%, the viscosity decreases instead. Therefore, it can be concluded that when the content of TX-100 is low, the shear thickening characteristics of TX-100 dominate, causing the viscosity of the slurry to increase with the content of TX-100; but when the content of TX-100 is higher, the dispersibility of TX-100 dominates again, making the slurry more uniform and the viscosity decreases instead.

[0040] (3) Effect of electrode composition on gram capacity:

[0041] In actual use, we hope that the energy density of lithium slurry batteries can be relatively high. For the electrodes of lithium slurry batteries, this means a higher gram capacity.

[0042] Taking lithium iron phosphate slurry as an example, the above (1) and (2) obtain the effect of different components on the viscosity and conductivity of lithium iron phosphate slurry. The gram capacity of lithium iron phosphate slurry under various component ratios is shown in Table 1 below (calculated based on the theoretical specific capacity of lithium iron phosphate of 170 mAh / g).

[0043] As the lithium iron phosphate content increases, the gram capacity also increases. Increasing the content of other components will reduce the gram capacity.

[0044] Table 1 Lithium iron phosphate slurry with different composition ratios and its viscosity (shear rate is 100 S -1 ), conductivity and gram capacity

[0045]

[0046] like Figure 2a , Figure 2b , Figure 2c , Figure 3a , Figure 3b , Figure 3c , Figure 3d , Figure 4a , Figure 4b , Figure 5a , Figure 5b , Figure 5c , Figure 6a , Figure 6b , Figure 6c , Figure 7a , Figure 7b , Figure 7c , Figure 7d , Figure 8a , Figure 8b , Figure 8c , Figure 8d , Figure 9a , Figure 9b , Fig.9c , Fig.10a , Fig.10b , Fig.10c As shown, according to the screening method described in this embodiment, through comprehensive evaluation of viscosity, conductivity and gram capacity, this embodiment obtains the component ratio after screening. The component ratio after screening is: 8% lithium iron phosphate, 1% Ketjen black, 2% TX-100, 89% electrolyte. Compared with other lithium iron phosphate slurries with different component ratios described in Table 1 above, this component ratio has better viscosity, conductivity and gram capacity.

[0047] This method of screening component ratios is not only applicable to lithium iron phosphate, but also to all electrode materials, including positive electrode materials such as lithium iron phosphate, ternary nickel cobalt manganese, organic positive electrode active materials, etc.; negative electrode materials such as lithium titanate, graphite and silicon, etc.

[0048] In addition, the present invention also discloses a method, which can further optimize the ingredient ratio according to the effect of different ingredients on viscosity, conductivity and gram capacity in combination with a numerical simulation method.

[0049] The present invention does not elaborate on some of the common technologies of those skilled in the art. The above-described embodiments are only descriptions of preferred implementations of the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementations described. Without departing from the design spirit of the present invention, various modifications and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the scope of protection determined by the claims of the present invention.

Claims

1. A lithium slurry battery electrode, characterized in that: The composition comprises the following components in percentage by mass: 8% lithium iron phosphate, 1% conductive agent, 2% dispersant and 89% electrolyte; The conductive agent is Ketjen black, the dispersant is TX-100, the electrolyte is a lithium bis(trifluoromethanesulfonyl)imide solution with a molar concentration of 1 mol / L, wherein the solvent is a mixture of dimethyl carbonate and ethylene carbonate, and the mixing ratio of dimethyl carbonate and ethylene carbonate is 7:3 by mass.

2. A lithium slurry battery electrode according to claim 1, characterized in that: The method for screening the composition ratio of the lithium slurry battery electrode comprises the following steps: Step 1: Determine the key indicators for screening the composition ratio of lithium slurry battery electrodes - conductivity, viscosity and gram capacity; Step 2: Obtain the effect of different components of the electrode on conductivity, viscosity and gram capacity; Step three, according to the action rules obtained in step two, the electrode composition ratio of the lithium slurry battery is screened.

3. A lithium slurry battery electrode according to claim 2, characterized in that: In step 1, the lithium slurry battery electrode is a slurry electrode composed of an electrode active material, a conductive agent and an electrolyte; The lithium slurry battery includes: the positive electrode and the negative electrode of the lithium slurry battery are both slurry electrodes; one of the positive and negative electrodes of the lithium slurry battery is a slurry electrode, and the other is a traditional solid electrode; the positive electrode material of the lithium slurry battery is lithium iron phosphate, ternary nickel cobalt manganese or an organic positive electrode active material, and the negative electrode material of the lithium slurry battery is lithium titanate, graphite or silicon.

4. A lithium slurry battery electrode according to claim 2, characterized in that: In step 2, the different components of the electrode are lithium-containing active material, conductive agent, dispersant and electrolyte.

5. A lithium slurry battery electrode according to claim 2, characterized in that: It also includes further optimization of the composition ratio according to the electrochemical performance requirements of the lithium slurry battery electrodes and the working mode of the lithium slurry battery.

Citation Information

Patent Citations

  • Novel lithium ion flow cell

    CN105206856A

  • Lithium slurry battery and negative plate thereof

    CN108242530A